2014
DOI: 10.1086/677156
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Risk Factors Identified for Patients Undergoing Colon Procedures, New York State 2009–2010

Abstract: Male sex, obesity, transfusion, type of procedure, and prolonged duration were significant factors associated with overall infection risk after adjusting other factors. Additional factors not collected in the NHSN slightly improved prediction of SSIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Some scholars investigated the mortality in patients experiencing postoperative nosocomial infection in the departments of general surgery. The results showed 7.5% mortality in patients with single-pathogen nosocomial infection and a mortality of 17.1% in patients with multiplepathogen mixed infection, which is higher than the average postoperative mortality of 0.53% (7).…”
Section: Introductionmentioning
confidence: 67%
“…Some scholars investigated the mortality in patients experiencing postoperative nosocomial infection in the departments of general surgery. The results showed 7.5% mortality in patients with single-pathogen nosocomial infection and a mortality of 17.1% in patients with multiplepathogen mixed infection, which is higher than the average postoperative mortality of 0.53% (7).…”
Section: Introductionmentioning
confidence: 67%
“…There are other studies demonstrating obesity to have a negative influence on complications. Several studies have identified a high risk of surgical site infection (SSI) with obesity . Similar adverse influences have been recognized for surgical procedures such as right hemicolectomy, LAR, Hartmann surgery, Miles surgery, and robotic surgery .…”
Section: Colorectal Surgerymentioning
confidence: 83%
“…Higher SSI proportions were reported after colon surgery with colostomy vs. no colostomy at a single hospital in Italy, (11) and left sided colectomy was independently associated with higher SSI risk compared to other colectomies in New York state hospitals. (12) Trans-tibial amputations had significantly higher 30-day deep incisional SSI risk than trans-femoral amputations in people ≥50 years old in a study by Hasanadka et al using data from the American College of Surgeons National Surgical Quality Improvement Program (NSQIP). (13) Olsen found that mastectomy plus immediate implant and mastectomy plus flap had higher 1-year SSI risk than mastectomy only at a tertiary care university hospital.…”
Section: Discussionmentioning
confidence: 99%